Lecturer Resistance To The Development Of Digital Technology In Learning In The Modern Education Era. - Lucky Antonio (International Journal of Christian Education and Philosophical Inquiry, 2024)
This study examines lecturers’ resistance to the development of digital technology in learning in the era of modern education. The purpose of the study was to identify barriers to explore factors that contribute to higher education resistance to the integration of digital technology in higher education. This method used a mixed methods approach , utilizing a survey to assess lecturers’ attitudes toward digital technology and interviews to provide deeper insights into personal experiences and perceived barriers. Data were analyzed using thematic analysis to identify common themes and patterns related to resistance with faculty members from various disciplines across institutions. The innovation in this study lies in a holistic approach that integrates faculty perspectives and institutional policies. And professional development and training on modern learning theories and the application of digital technologies in education. The results of this study underscore the need for tailored support and training initiatives to improve skills and confidence in the use of digital technologies so as to address specific issues and barriers identified by faculty by integrating technology into teaching towards effectiveness and can improve student learning experiences in this increasingly digital era.